Analysis of nocturnal actigraphic sleep measures in patients with COPD and their association with daytime physical activity. Issue 8 (12th January 2017) - Spina, Gabriele; Spruit, Martijn A; Alison, Jennifer; Benzo, Roberto P; Calverley, Peter M A; Clarenbach, Christian F; Costello, Richard W; Donaire-Gonzalez, David; Dürr, Selina; Garcia-Aymerich, Judith; van Gestel, Arnoldus J R; Gramm, Marco; et al.
Abstract : Background: Sleep disturbances are common in patients with chronic obstructive pulmonary disease (COPD) with a considerable negative impact on their quality of life. However, factors associated with measures of sleep in daily life have not been investigated before nor has the association between sleep and the ability to engage in physical activity on a day-to-day basis been studied. Aims: To provide insight into the relationship between actigraphic sleep measures and disease severity, exertional dyspnoea, gender and parts of the week; and to investigate the association between sleep measures and next day physical activity. Methods: Data were analysed from 932 patients with COPD (66% male, 66.4±8.3 years, FEV1 % predicted=50.8±20.5). Participants had sleep and physical activity continuously monitored using a multisensor activity monitor for a median of 6 days. Linear mixed effects models were applied to investigate the factors associated with sleep impairment and the association between nocturnal sleep and patients' subsequent daytime physical activity. Results: Actigraphic estimates of sleep impairment were greater in patients with worse airflow limitation and worse exertional dyspnoea. Patients with better sleep measures (ie, non-fragmented sleep, sleeping bouts ≥225 min, sleep efficiency ≥91% and time spent awake after sleep onset <57 min) spent significantly more time in light (p<0.01) and moderate-to-vigorous physical activity (p<0.01). Conclusions: There is a relationship between measures of sleep in patients with COPD and the amount of activity they undertake during the waking day. Identifying groups with specific sleep characteristics may be useful information when designing physical activity-enhancing interventions.